Pengaruh Tingkat Kesehatan Bank Terhadap Pertumbuhan Laba Pada Bank Go-Publik Di Bursa Efek Indonesia (BEI) Tahun 2014-2016 - Nugroho, Tatas Ridho (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2018)
Bank soundness is the result of the assessment of various aspects that affect the condition or performance of a bank through the assessment of factors such as Capital, Asset Quality, Management, Earning, and Liquidity Sensitivity to Market Risk. The purpose of this study is to determine the effect of bank soundness on earnings growth in bank Go - Public In Indonesia Stock Exchange (BEI) Year 2014-2016. The research method used in this research was multiple linier regression analysis method. The type of data used in this study was quantitative and the data source used included in the secondary data. The variables that become the object of this research are Capital Adequancy Ratio (CAR), Operational Efficiency (BOPO), Loan to Deposit Ratio (LDR), Interest Risk Ratio (IRR), and Profit Growth (Y). Analytical technique used to analyze the data that formed the numbers compared to one another then analyzed by used multiple linear regression test statistic. Simultaneously CAR (X1), BOPO (X2), LDR (X3) and IRR (X4) variables have an effect on profit growth with p value 0.000, partially CAR, LDR and IRR variables significantly influence profit growth, while BOPO partially does not give effect. The magnitude of the effect of independent variables on profit growth (Y) of 0.926 or 92.6% while the rest of 7.4% influenced by other variables not included in this study. Among the 4 independent variables, namely CAR (X1), BOPO (X2), LDR (X3) and IRR (X4), which dominantly influence the dependent variable of profit growth are CAR (X1) variables.